(untitled) (Research, Society and Development, 2021)
Looking for alternative sources in animal nutrition, microalgae began to be explored, gaining space in commercial production. The aim of this review is to present available information about the use of microalgae in animal nutrition, as well as its effect and applications. Many microalgae are important sources of polyunsaturated fatty acids (PUFA), mainly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). These PUFA is poorly synthesized by animals, so they should be included in their diet. In addition, they are a rich source of almost all of the important minerals as well as vitamins. Additionally, some microalgae generally have a high protein content and high digestibility. In this context, microalgae already available on the market, become an alternative replacing conventional ingredients. To our knowledge, the use of small amounts of microalgae biomass in the feed can benefit the physiology of the animals, improving the immune response, resistance to diseases, antiviral and antibacterial action, intestinal function, and stimulation of probiotic colonization. In general, the addition of these compounds to the diets of animals enhances their overall health and immune status, productivity, and the quality and stability of the resulting animal products. Although the use of microalgae is increasingly directed towards many types of animals: cats, dogs, ornamental fish, horses, poultry, swine, sheep, and cow, studies still need to be explored.